Invariant Subspace and Classification of Soliton Solutions of the Coupled Nonlinear Fokas-Liu System - Aliyu, Aliyu Isa; Li, Yongjin; Baleanu, Dumitru (Frontiers in Physics, 2019)
In this work, the coupled nonlinear Fokas–Liu system which is a special type of KdV equation is studied using the invariant subspace method (ISM). The method determines an invariant subspace and construct the exact solutions of the nonlinear partial differential equations (NPDEs) by reducing them to ordinary differential equations (ODEs). As a result of the calculations, polynomial and logarithmic function solutions of the equation are derived. Further more, the ansatz approached is utilized to derive the topological, non-topological and other singular soliton solutions of the system. Numerical simulation off the obtained results are shown.